Problem-solving mathematical ability in statistics courses: The impact of the Think-Pair-Share strategy assisted by R software - Sri Sukmawati; Ratu Khoirotun Nisa (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
Problem-solving ability has been recognized as a key competency in 21st-century learning, particularly in statistics education, where students are required to analyze data and interpret results accurately. Integrating digital tools such as R software is considered essential for supporting these competencies, as they enable students to explore data, perform computations, and visualize outputs effectively. This study aimed to examine the effectiveness of the Think-Pair-Share model assisted by R software (TPS-R) in improving students' problem-solving abilities in statistics courses. A quantitative approach using a quasi-experimental design was employed, involving two groups: an experimental class applying TPS-R and a control class applying the Think-Pair-Share model without R software (TPS-WR). The results showed a significant difference in problem-solving abilities between the two groups, with the TPS-R class demonstrating higher performance (Mann-Whitney U = 215.0, Z=−2.428, p = 0.017). These findings indicate that integrating TPS with R software serves as an effective instructional strategy in statistics courses, provided that instructors manage class time efficiently and guide students' learning processes appropriately.